2008
DOI: 10.1016/j.jmb.2008.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Substrate Specificity in Plant 5′-Methylthioadenosine Nucleosidases

Abstract: 5'-Methylthioadenosine (MTA)/S-adenosylhomocysteine (SAH) nucleosidase (MTAN) is essential for cellular metabolism and development in many bacterial species. While the enzyme is found in plants, plant MTANs appear to select for MTA preferentially, with little or no affinity for SAH. To understand what determines substrate specificity in this enzyme, MTAN homologues from Arabidopsis thaliana (AtMTAN1 and AtMTAN2, which are referred to as AtMTN1 and AtMTN2 in the plant literature) have been characterized kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 57 publications
1
30
1
Order By: Relevance
“…MTN1 N113 is involved in ligand binding via coordination of a water molecule in the ligand-binding pocket (Fig. 5A) (71). MTN1 N194 and MTN1 N169 are both surface exposed at the end of helices α4 and α3, respectively (Fig.…”
Section: Mutation Of Two Conserved Mtn Asparagine Residues To Deamidamentioning
confidence: 99%
“…MTN1 N113 is involved in ligand binding via coordination of a water molecule in the ligand-binding pocket (Fig. 5A) (71). MTN1 N194 and MTN1 N169 are both surface exposed at the end of helices α4 and α3, respectively (Fig.…”
Section: Mutation Of Two Conserved Mtn Asparagine Residues To Deamidamentioning
confidence: 99%
“…Recently, it has also been shown that both MTNs are abundant in the phloem tissue (Pommerrenig et al, 2011). Although MTN1 and MTN2 polypeptides share 64% amino acid sequence identity, they have distinct substrate specificities and pH optima (Siu et al, 2008). Thus, it was initially inferred that these two enzymes may have distinct roles in plant metabolism: in vitro, MTN1 accepts only MTA as a substrate, while MTN2 can also accept S-adenosylhomocysteine to a limited extent (Siu et al, 2008).…”
mentioning
confidence: 99%
“…Although MTN1 and MTN2 polypeptides share 64% amino acid sequence identity, they have distinct substrate specificities and pH optima (Siu et al, 2008). Thus, it was initially inferred that these two enzymes may have distinct roles in plant metabolism: in vitro, MTN1 accepts only MTA as a substrate, while MTN2 can also accept S-adenosylhomocysteine to a limited extent (Siu et al, 2008). More recent crystallography and protein dynamic analyses revealed that MTN1 binds to S-adenosylhomocysteine but is incapable of hydrolyzing it (Siu et al, 2011).…”
mentioning
confidence: 99%
“…Many plant MTAN homologues are unable to metabolize SAH and those that do show 84–87% reduction in activity relative to the hydrolysis of MTA (Guranowski et al, 1981; Rzewuski et al, 2007; Baxter and Coscia, 1973). Kinetic characterization of the two MTAN homologues found in the thale cress plant, Arabidopsis thaliana, showed that At MTAN1 is completely inactive towards SAH while At MTAN2 has 14% activity towards this substrate (Siu et al, 2008a). Structural comparison of At MTAN1 with the bacterial MTAN homologue from Escherichia coli ( Ec M-TAN) showed significant conservation in the overall structure (Siu et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic characterization of the two MTAN homologues found in the thale cress plant, Arabidopsis thaliana, showed that At MTAN1 is completely inactive towards SAH while At MTAN2 has 14% activity towards this substrate (Siu et al, 2008a). Structural comparison of At MTAN1 with the bacterial MTAN homologue from Escherichia coli ( Ec M-TAN) showed significant conservation in the overall structure (Siu et al, 2008a). Close examination of the active sites suggested that the active site of Ec MTAN may be more disordered than that of At MTAN1 (Siu et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%